Pemberdayaan Masyarakat melalui Program Peningkatkan Usaha Mikro Kecil Menengah Kampung Pentol di Kelurahan Sidotopo, Surabaya - Tito Mariano; Andika Prasetio; Moh. Musleh (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Sidotopo Urban Village, Surabaya City, precisely in RT 06 RW 10, there are Micro, Small and Medium Enterprises (MSMEs) that produce products in the form of pentol snacks, business capital for production is the main problem for UKM pentol in the area. The Pentol Village MSME community empowerment program in the Sidotopo Village was held to provide solutions to the economic problems that have been faced so far. The implementation of community empowerment will be carried out in October 2022 and there are several process stages of activities carried out, including: the socialization of the pentol village program in Sidotopo Village, Surabaya City; forming a partnership group for pentol producers; building cooperation; as well as providing pentol production tools and carts for the distribution of pentol production. Through the empowerment process carried out by the Gugah Nurani Indonesia Foundation (GNI) as a non-governmental organization through the pentol village program for the UMKM pentol producers, it is able to have a positive impact in the form of knowledge related to business capital management and management of pentol business income and expenses, and is able to increase additional income from MSMEs that are optimized by providing training education.